2018
DOI: 10.1111/are.13870
|View full text |Cite
|
Sign up to set email alerts
|

Orange peel fragment improves antioxidant capacity and haematological profile of Nile tilapia subjected to heat/dissolved oxygen‐induced stress

Abstract: This study evaluated the ability of orange peel fragment (OPF) to act as a functional feedstuff, influencing growth, haematological profile, and antioxidant enzyme activity of Nile tilapia subjected heat/dissolved oxygen-induced stress (HDOIS). A group of 440 male Nile tilapia (31.7 g ± 0.34) was randomly distributed in 40 250-L aquaria (11 fish/tank) and fed five practical diets with graded levels of OPF at 0%, 0.2%, 0.4%, 0.6%, and 0.8% for 70 days. The diets were formulated to contain 30% crude protein and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…The erythrogram (Hb, RBCs and PCV) of Nile tilapia fed OEO and/or LEO supplemented diets showed non‐significant difference and was within the normal range of tilapia (Mohamed et al., 2017). It indicated that OEO and/or LEO had no negative effect on health status of cultured fish (Acar et al., 2019; Vicente et al., 2019). Dissimilar, RBC and PCV are increased with increasing dietary supplementation of EO extract from Citrus limon fruit peels from 1% to 5% (Ngugi et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The erythrogram (Hb, RBCs and PCV) of Nile tilapia fed OEO and/or LEO supplemented diets showed non‐significant difference and was within the normal range of tilapia (Mohamed et al., 2017). It indicated that OEO and/or LEO had no negative effect on health status of cultured fish (Acar et al., 2019; Vicente et al., 2019). Dissimilar, RBC and PCV are increased with increasing dietary supplementation of EO extract from Citrus limon fruit peels from 1% to 5% (Ngugi et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Stress can interfere with the balance between oxidation systems and antioxidants because of excessive formation of reactive oxygen species (ROS) or reduction of antioxidant (Salem et al., 2019). Therefore, the use of EOs extracted from some fruits or plants as nutritional additives has drawn much worldwide publicity and several studies have been conducted indicating its role in diseases control, improving growth performance, nutrient absorption and immune response (Toutou et al., 2018; Vicente et al., 2019). Although the important role of EOs in fish growth and development is well known, the information on synergistic effects of EOs extract from bitter lemon ( Citrus limon ) and sweet orange ( Citrus sinensis ) peels on Nile tilapia under aquaculture conditions is very rare.…”
Section: Introductionmentioning
confidence: 99%
“…In fact , carotenoids, a vital constituent of orange peel, possess a peroxyl radical scavenging activity, which protects lipoproteins and cellular membranes against ROS (Rodrigo et al, , ; Stahl & Sies, ). In support, Vicente et al () studied the ability of orange peel to act as a promoter for antioxidant enzymes activity of Nile tilapia subjected heat/dissolved oxygen‐induced stress, which fed five diets with graded levels of OP at 0, 2, 4, 6, and 8 g/kg diet. The results suggested that dietary orange peel improved superoxide dismutase, catalase and glutathione peroxidase activities of Nile tilapia under stress.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that the diversity of bioactive compounds identified in the banana peel, such as phenolic acids, flavonoids, and carotenoids, is responsible for improving the hepatic antioxidant response in rohu. Furthermore, Vicente et al [ 95 ] evaluated the effect of orange peel fragment (OPF), as a food additive, on the antioxidant enzyme activity of Nile tilapia subjected to heat/dissolved oxygen-induced stress. In the study, fish were fed diets with different inclusion of OPF (0, 0.2, 0.4, 0.6, and 0.8%) for 70 days.…”
Section: Use Of Bioactive Compounds From Agro-industrial Waste In mentioning
confidence: 99%